THE EFFECT OF THE COMPARISON OF MORINGA OLEEFERA ( Moringa oleifera) AND ROSELA ( Hibiscus sabdariffa ) LEAVES IN KOMBUCHA TISANE ON ANTIOXIDANT ACTIVITY, PH VALUE, AND ORGANOLEPTICS - Rizka Andrea Safira; Retnani Rahmiati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Kombucha is a fermented beverage produced from bacteria and yeast. Moringa leaves are herbs that have long been known for their various benefits. Roselle is a plant with red petals and high anthocyanin content. This study aims to determine the effect of the ratio of moringa and roselle leaves on the antioxidant activity of kombucha and to determine the optimal ratio for kombucha antioxidant activity. The research method used was a laboratory experiment with a Completely Randomized Design (RUPS), which consisted of treatments with various concentrations of moringa and roselle leaves, namely 90%:10%, 80%:20%, 70%:30%, and 60%:40%. The variables observed were antioxidant activity using the DPPH method, pH levels using a pH meter, and organoleptic quality. Parametric data obtained were analyzed using ANOVA and if there were significant differences, continued with the DMRT test. Non-parametric data were analyzed using the Kruskal Wallis method. The results showed that increasing the concentration of moringa leaves significantly increased antioxidant activity, pH, and decreased taste. However, there were no significant differences in color and aroma. The De Garmo method identified 90% moringa leaves and 10% roselle flowers as the optimal formulation with an antioxidant inhibition value of 82.63%, a pH of 3.567, and organoleptic scores of color 3, taste 1, and aroma 2.